Challenges Faced by Micro, Small and Medium Enterprises in Chennai City : Starting or Growing a Business - Ramkumar, Gowtham (AMC Indian Journal of Entrepreneurship, 2019)
The Government of India has been taking various economic steps to raise the pace of economic growth of our country. Demonetization and Goods and Services Tax are also considered as part of such economic reforms done by the government. The growing changes in the Indian economy and also the business environment have significant impact on various sectors operating in our country. MSMEs are no exception to these changes. While some experts see these economic reforms as an opportunity for MSMEs to grow, others have unfavorable opinions. Government of India is also taking various steps and introducing various schemes to make India as the place of ease of doing business. With these changing economic conditions, this paper lists out the various challenges faced by MSMEs specifically while starting and growing their business in Chennai city.